Nghiên cứu tổng hợp gefitinib làm nguyên liệu bào chế thuốc điều trị ung thư phổi - Trường, Vương Văn; Kha, Hoàng Như; Thùy Trang, Đỗ Thị; Nam, Phạm Duy; Ngọc, Nguyễn Văn; Quân, Trần Đức; Hoàng, Dương Đức (Vietnam Journal of Chemistry, 2015)
Gefitinib is an anilinoquinazoline which is useful in the treatment of a certain type of lung cancer (non-small cell lung cancer - NSCLC) that has not responded to chemotherapy. In this paper, we report results of synthesis of gefitinib and intermediates. Structure of gefitinib and its intermediates was confirmed by spectroscopic methods such as IR, 1H NMR, 13C NMR and MS.